Healthcare Costs Associated with Potentially Inappropriate Medication Prescribing Detected by Computer Algorithm Among Older Patients - Pagès, Arnaud; Costa, Nadège; Mounié, Michaël; Cestac, Philippe; De Souto Barreto, Philipe; Rolland, Yves; Vellas, Bruno; Molinier, Laurent; Juillard-Condat, Blandine (Drugs & aging, 2022)
Introduction Potentially inappropriate medication prescribing (PIP) among older patients is associated with an increased risk of adverse events and hospitalization, and sometimes increased healthcare costs. Objective The aim of this study was to explore the association between healthcare costs and PIP exposure among older patients. Methods Analyses were conducted using data from the Multidomain Alzheimer Preventive Trial (MAPT). A computer algorithm was constructed to detect PIP based on various different explicit criteria-based tools, and the results were expressed in number of medication-related potential non-compliances (MRNCs). A prescription was considered potentially inappropriate if there were one or more MRNCs. We performed a cost analysis from the French National Health Insurance perspective, and also performed a multivariate analysis to identify the association between healthcare costs and PIP (number of MRNCs). Results The computer algorithm analyzed medication prescribing from included patients ( N = 1525 aged 75.3 ± 4.4 years; 64% women [ n = 978]). PIP was associated with increased total healthcare costs and non-medication healthcare costs after adjusting for potential confounders. We also noted that healthcare costs tended to increase with the number of MRNCs. The mean additional healthcare costs were €517, €921, and €1669 per patient and year for patients with one or two MRNCs, three or four MRNCs, and five or more MRNCs, respectively, in comparison with patients with appropriate medication prescriptions. Conclusion These observations led us to conclude that interventions focused on reducing PIP could result in savings. Trial Registration ClinicalTrials.gov: NCT00672685.